Eosinophilic gastroenteritis as the initial manifestation of hypereosinophilic syndrome. - Narisa SS; Shanti P; Jeevinesh NA; Sakthiswary R (Penerbit UKM, 2013)
Eosinophilic gastroenteritis, an inflammatory disease of unknown etiology, commonly involves the stomach and small intestine with eosinophilic infiltration. Here, we report an unusual case of eosinophilic gastroenteritis involving the entire digestive tract as a manifestation of hypereosinophilic syndrome (HES). A 22-year-old woman presented to us with diarrhoea, pleural effusion, ascites and marked peripheral oeosinophilia. Stool specimens were negative for parasites, ova, bacteria, and fungi. Endoscopic studies showed pangastritis and duodenitis. Biopsy specimens of the oesophagus, stomach, duodenum, ileum, and colon demonstrated oeosinophilic infiltration. A diagnosis of hypereosinophilic syndrome with eosinophilic gastroenteritis involving the entire digestive tract was made. Hence, she was treated with prednisolone. Symptoms and peripheral oeosinophilia rapidly resolved with treatment, and radiological investigations revealed resolution of effusion. This case illustrates the wide spectrum of clinical manifestation of the disease, whereby it involves the entire digestive tract and it also emphasizes the diagnostic yields of endoscopic biopsies.